INFLUENCE OF TA’AWUN (MUTUAL COOPERATION) IN SUSTAINING INNOVATION ALLIANCES (International Journal of Islamic Business, 2023)
Companies use cooperative strategies in sustaining performance and competitive advantage. The driver behind the cooperative strategies is mutual cooperation. There is an integration in the inter-companies’ alliances at horizontal level. The inter-companies’ alliances provide platforms and coworking spaces for value creation and innovation. This purpose of the study is to explore the influence of ta’awun (mutual cooperation) in sustaining innovation alliances. The study used personal interview with key managerswith manual data collection and data analysis. The key results suggested that the influence of ta’awun is the spirituality and social driven on the contractual arrangements in the alliances. The main theoretical contribution is the alliances with spiritual cooperation through unified socialization.